2000
DOI: 10.1590/s0066-782x2000000100008
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of infectious diseases through mouth-to-mouth ventilation: evidence-based or emotion-based medicine?

Abstract: UpdateCardiopulmonary arrest is the interruption of the heart's mechanical activity confirmed by unconsciousness, apnea, and absence of central pulse 1 . The basic technical knowledge for management of this medical emergency by way of cardiopulmonary resuscitation (CPR) should be part of the training curriculum for health care workers and is highly recommended for the general public. However, concern about the transmission of diseases appears to have created substantial barriers for the use of CPR, both in and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 140 publications
0
18
0
3
Order By: Relevance
“…Although CPR is deemed as a safe, effective technique capable of saving lives, many rescuers fail in performing CPR due to fear of acquiring infectious-contagious diseases by means of mouth-to-mouth respiration (3,9,10) . In fact, several infectious diseases can be transmitted during any mouth-to-mouth contact, but in spite of the transmissibility potential, literature records very rare cases of effective contagious processes during the execution of CPR maneuvers in over 250 years (10) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CPR is deemed as a safe, effective technique capable of saving lives, many rescuers fail in performing CPR due to fear of acquiring infectious-contagious diseases by means of mouth-to-mouth respiration (3,9,10) . In fact, several infectious diseases can be transmitted during any mouth-to-mouth contact, but in spite of the transmissibility potential, literature records very rare cases of effective contagious processes during the execution of CPR maneuvers in over 250 years (10) .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several infectious diseases can be transmitted during any mouth-to-mouth contact, but in spite of the transmissibility potential, literature records very rare cases of effective contagious processes during the execution of CPR maneuvers in over 250 years (10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…105 No case of transmission by HCV after mouth-to-mouth ventilation has been described. 106 Transmission of HCV in CPR using CPR mannequins has not been reported even when exposed to HCV-contaminated saliva. 107 Saliva may therefore be a source of occasional transmission of HCV, 108 particularly where there is deep kissing and there are oral mucosal lesions 109 though epidemiological studies suggest that the infective capacity of HCV in saliva is only low.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Disease transmission is only occasionally reported after CPR (7,8). In a meta-analysis from year 1998, Mejicano and Maki found that only 15 documented cases, mainly bacterial infections, were reported after mouthto-mouth ventilation.…”
Section: Introductionmentioning
confidence: 99%